SEJARAH DAN PROSESI TRADISI ADAT BALALA’ SUKU DAYAK KANAYATN - Andang Firmansyah; Edwin Mirzachaerulsyah; Irena Yovanka T.A. (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2021)
Balala' traditional ceremony is one of forbidden customs in the Kanayatn Dayak community. This study describes the Balala' indigenous traditions held by Dayak Kanayatn tribe in Pate Hamlet, Saham Village, Sengah Temila District, Landak Regency. The research method used is a descriptive qualitative one with an ethnographic approach, while the data collection techniques used are interviews and documentation. Data collection instruments are interview guides and documentation. Based on the research results, the ‘Balala' traditional procession consists of several stages: Mansorokng ceremony held on April 12, opening ceremony on May 28, and ‘Bungkas Lala’ ceremony on May 31. This rite is a form of ceremony to get rid of bad luck or bad things. Every citizen always obeys advices and prohibitions. This paper implies that the ‘Balala' customary tradition can be known widely, especially to the younger generation in order to be preserved as it represents the personal awareness of the community as indigenous peoples.